2022
DOI: 10.1186/s12909-022-03480-x
|View full text |Cite
|
Sign up to set email alerts
|

One academic year under COVID-19 conditions: two multicenter cross-sectional evaluation studies among medical students in Bavarian medical schools, Germany students’ needs, difficulties, and concerns about digital teaching and learning

Abstract: Background Since March 2020, COVID-19 has created a need for adaptation in many areas of life. This study explores medical students’ perspectives on digital teaching under conditions of the COVID-19 pandemic. It focuses on expectations and concerns about digital teaching, the evaluation of specific aspects of teaching, and requests for future teaching. Methods Six German faculties have joined forces within the Bavarian network for medical education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…These results are in accordance with those of similar cross-sectional studies from other countries. A multicenter cross-sectional study among German medical students [ 31 ] revealed similar concerns about poor exchange between fellow students and with teachers as well as the lack of practical training. Additionally, a proportion of students was unable to participate in DL due to the lack of adequate devices.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with those of similar cross-sectional studies from other countries. A multicenter cross-sectional study among German medical students [ 31 ] revealed similar concerns about poor exchange between fellow students and with teachers as well as the lack of practical training. Additionally, a proportion of students was unable to participate in DL due to the lack of adequate devices.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the pandemic, the establishment of digital teaching formats was often viewed negatively from the point of view of the lecturers since the implementation was a major challenge for the lecturers and the medical universities ( 21 ). At the beginning of the establishment of digital teaching concepts, the students had a positive attitude, although this attitude changed over the course of the pandemic years ( 22 ). The once divergent picture between lecturers and students is getting closer over the course of time.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study focusing on the impact of the COVID-19 pandemic on workload, work content, and related challenges among the public health workforce in Germany, which includes data on students and young professionals. Previous studies in the context of the COVID-19 pandemic have either focused on specific aspects -particularly related to digital teaching -within medical students or healthcare personnel [22][23][24] or on mental health issues due to social isolation [1,25]. Although knowledge is available that as an adverse effect of the COVID-19 pandemic education and job training have been disrupted or delayed for many young adults and traditional ways of working encountered serious challenges [26], there has been limited attention on the public health workforce [27,28] in Germany.…”
Section: Discussionmentioning
confidence: 99%